METHODOLOGICAL RECOMMENDATIONS FOR ORGANIZING INDEPENDENT WORK OF STUDENTS IN THE PROCESS OF TEACHING ENGLISH (Scientific journal of the Fergana State University, 2024)
This article examines the need to form skills and develop the abilities of independent professional educational activities, which is the basis for further university self-education. It reveals that independent work on the subject “Foreign Language” allows a future specialist to be involved in research activities using foreign language means, develops such important skills as searching for professionally relevant information, analyzing it and highlighting the main content in the text, assessing the informativeness of the material and professional oriented communication based on the information received.